Adoção de uma abordagem neopiagetiana e de padrões de abstração para o ensino de Engenharia de software: proposição de um modelo pedagógico de correlação entre o alinhamento construtivo e a técnica OC2-RD2 - Vendramel, Wilson (2023)
Considering that software systems are essential for several fields of knowledge, teaching software engineering becomes crucial for building quality programming products for society. This implies a demand for qualified students throughout life, given that the quality of teaching has an impact on improving the software development process. Computing and informatics students often need to use abstractions, build mental analysis and design models, and adequately represent them in the many and diverse artifacts produced during the software life cycle, however, on the other hand, the diversity of purposes, forms and levels of abstraction are not easily understood. The theoretical repertoire of software engineering is vast, complex, and full of concrete and abstract concepts, therefore, it is significant to have an appropriate pedagogical environment for teaching this area of computing. Although a large part of piagetian theory deals with the learning of children and adolescents, piagetian theoretical principles have been extended to adult learning, as is the case of the neo-piagetian theory that expands the classic piagetian view in several areas, where one of the perspectives is that stages of cognitive development extend beyond childhood and continue into adulthood when applied to new cognitive contexts. Given the above, this study investigates a gap related to the teaching of software engineering, with the aim of allowing students to reach levels of increasing cognitive complexity in the construction of concrete and abstract knowledge. To this end, the objective of this work is to propose a pedagogical model built from the correlation between the constructive alignment and the organizational plans of the OC2-RD2 technique, in order to assist the teacher in planning software engineering teaching. The proposed model is inspired by a neo-piagetian vision, supported by the learning verbs of the SOLO cognitive taxonomy, as well as by a collection of abstraction patterns that aim to strengthen abstract thinking, aspiring, in this way, to develop this cognitive capacity, considered a skill -key for students of courses in the computational area. This study has a qualitative approach, exploratory purpose and applies the semi-structured interview as a research tool. The interview script was applied to a sample of teachers from different educational institutions. Data from the knowledge and experience of the professors were analyzed and interpreted, resulting in the construction of a pedagogical model (metamodel) for teaching software engineering, specifically for the area of software modeling and analysis. This metamodel consists of a set of thematic and reusable ontological plans of content and cognition, as well as constructively aligned, in order to guide the teacher, from the point of view of cognitive development and learning progression, in the planning of engineering courses and classes of software in different times and spaces